(untitled) (Journal of the College of Basic Education, 2022)
Zinc oxide ZnO thin films were deposited by DC magnetron sputtering technique on preheated glass substrates at 500 , and subsequently the effect of β- particles produced from 90Sr source on the optical properties of the films was investigated. The optical properties of the films have been characterized using spectrophotometric measurements of transmittance and absorbance at the normal incidence of light in the wavelengths range over 380-900 nm. The absorption coefficient, optical energy gap, Urbach energy, optical constants (refractive index, extinction coefficient, dielectric constant) and dispersion parameters, such as single-oscillator energy, dispersive energy for un-irradiated and the